The effectiveness of remedial courses: the case of undergraduate students in industrial engineering - Sgobbi, Francesca (2020)
Under-preparation is one of the main causes behind poor academic performance by under-graduate students. Higher education institutions often launch remedial courses as an inclusive solution to help academically deprived freshmen fill their knowledge gaps. However, the substantial resources absorbed by remedial courses raise recurrent concerns about their suitability. This paper exploits 2012-2016 administrative data from a medium-size university in Northern Italy to appraise the effectiveness of the remedial courses undertaken by newly enrolled students in industrial engineering who fail to achieve the entry test cut-off score. The outcomes of the empirical analysis provide an articulated picture. The two-year drop-out rate of students who successfully complete a remedial course is not statistically different from that of nonremedial students, whereas significant differences persist in the number of earned credits. However, in two years also this difference disappears when the control group restricts to students who could enrol in an undergraduate course without need for remedial education thanks to a performance just above the cut-off score.